Accessibility to Non-COVID Health Services in the World During the COVID-19 Pandemic: Review - Tuczyńska, Magdalena; Matthews-Kozanecka, Maja; Baum, Ewa (Frontiers in Public Health, 2021)
Background: COVID-19 pandemic caused by SARS-CoV2 has seriously impacted the global economy. Medical facilities around the world were not prepared for the enormous challenges posed by the growing number of patients each day, the shortage of personal protective equipment, and insufficient numbers of medical staff. Governments have tried to counteract the impact of the pandemic, but the measures taken have not always been sufficient to maintain access to and quality of health services at the same level as before the pandemic. The disruption of health services has resulted in more and more research reports from different parts of the world on the accessibility of health services during the COVID-19 pandemic. Methodology: This review article presents 21 selected scientific studies on access to health services in different regions of the world. Articles were found in PubMed, GoogleScholar, Medline, and ScienceDirect databases, then grouped, and significant data were extracted from each article. The results were summarized in a table. Results: The range of limited health services included a variety of specialties, including primary care, psychiatry, orthopedics, cardiology, neurosurgery, and more. Methods used in the studies were based on retrospective analysis or on the subjective assessment of patients in the form of a questionnaire or interview. Most authors claimed a decrease in accessibility to health services during the COVID-19 pandemic compared to the pre-pandemic period, including a decrease in planned surgeries, doctor appointments, patient admission to hospital or ER, and access to medicines. Additionally, some authors observed an increase in the mortality rate. One of the few medical services that have expanded rapidly during the pandemic was online appointments. Conclusions: The COVID-19 pandemic has most certainly affected the accessibility of health services worldwide. Lessons should be learned to prevent inaccessibility to medical services, especially as experts predict another wave of COVID-19 cases.